2011
DOI: 10.3390/polym3031565
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Two Related Metal-Organic Frameworks (MOFs), [Cu2(bdc)2(dabco)] and [Cu2(ndc)2(dabco)], with Ferrocene

Abstract: Abstract:We have studied the loading of two related, similar porous metal-organic frameworks (MOFs) [Cu 2 (bdc) 2 (dabco)] (1), and [Cu 2 (ndc) 2 (dabco)] (2) with ferrocene by exposing bulk powder samples to the corresponding vapor. On the basis of powder X-ray diffraction data and molecular dynamics (MD) calculations we propose that each pore can store one ferrocene molecule. Despite the rather pronounced similarity of the two MOFs a quite different behavior is observed, for 1 loading with ferrocene leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In fact, CPs can be easily functionalized via the postsynthetic introduction of various functional groups (e. g., Fc units) to achieve specific properties not directly accessible by conventional methods of CP synthesis. [65,75,76] For instance, Fc-containing organic ligands can be used to construct porous Fc-based MOFs. [77,78] On the other hand, many studies relied on the postsynthetic linking of Fc derivatives to the MOF backbone to prepare redox-active MOFs.…”
Section: Postsynthetic Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, CPs can be easily functionalized via the postsynthetic introduction of various functional groups (e. g., Fc units) to achieve specific properties not directly accessible by conventional methods of CP synthesis. [65,75,76] For instance, Fc-containing organic ligands can be used to construct porous Fc-based MOFs. [77,78] On the other hand, many studies relied on the postsynthetic linking of Fc derivatives to the MOF backbone to prepare redox-active MOFs.…”
Section: Postsynthetic Methodsmentioning
confidence: 99%
“…This result is important for the electronic applications of insulator MOFs. [75] In 2011, Heck et al reported the incorporation of Fc into [Cu 2 (ndc) 2 (dabco)] and [Cu 2 (bdc) 2 (dabco)] upon exposure to Fc vapor and showed that the slower diffusion of Fc into [Cu 2 (ndc) 2 (dabco)] pores is due to the grandeur of the ndc ligand. The loaded Fc molecules did not undergo any chemical redox reaction immediately upon impregnation and could therefore act as redox-active sites.…”
Section: Postsynthetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 This strategy was utilized to synthesize analogues of MOF-74, Mn 2 (DSBDC)(DMF) 2 , where thiolated ligand H 4 DSBDC forms an innite 1D metal-sulfur chain (-M-S-in contrast to typical -M-Ochains in MOF-74) that act as the charge transport pathways. 12 Method (2) of addressing MOF's conductivity is by loading redox active compounds (ferrocene, iodine, and tetracyanoquinodimethane) [13][14][15] introduced either during the synthesis or infused in various post-synthetic treatments. As a result, redox active sites are created inside the MOF's structure which help facilitate charge transfer.…”
Section: Introductionmentioning
confidence: 99%